PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU KERJA KARYAWAN - Rahayu, Vinona Vamalya; Chaniago, Harmon (POLITEKNIK NEGERI BANDUNG, 2016)
Manage the human resources that are owned by the company. Quality leadership is often regarded as one of the important factors in the success or failure of the enterprise. Leadership style is often done at the company leader is transformational leadership style. Leaders with transformational leadership giving effect to the subordinates to include her participation in goal setting, problem-solving, decision making, and provide feedback. Leadership style leader can influence the behavior of its employee's work. This study aims to determine how the transformational leadership style, employee behavior and the effect of transformational leadership style on the behavior of employees at Suzuki Dealer Restu Mahkota Karya Cibadak. The method used in this research is a descriptive method, while the data collection techniques are to do interviews and distributing questionnaires to 102 respondents who were determined by non-probability sampling. Based on the research that has been done, regression equation Y = 0.874 + 0,807X. The study states that the transformational leadership style and behavior of existing employees at the Suzuki Dealer Cibadak Restu Mahkota Karya has a positive correlation of 0.807 and transformational leadership style influence the behavior of the employee as much as 65%.